2018
DOI: 10.15208/beh.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Solving global problems: Waste to power while creating stakeholder shared value

Abstract: In 2015, an estimated 1.2 billion people, or 16% of the global population, did not have access to electricity. At the same time, solid waste generation rates have risen fast, reaching 30 million tons in 1980, 200 million tons today, and projected to exceed over 11 million tons per day by 2100. The waste from cities alone is already enough to fill a line of trash trucks 5,000 kilometers long every day. Solutions, therefore, must be found, with Waste to Energy (WtE) conversion a strong contender, which presently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Governance Corporate social responsibility Good ethical and responsible business practices, both socially and environmentally, that lead to sustainable development. [12,16] Transparency in the solid waste management…”
Section: Key Success Factors Definition Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Governance Corporate social responsibility Good ethical and responsible business practices, both socially and environmentally, that lead to sustainable development. [12,16] Transparency in the solid waste management…”
Section: Key Success Factors Definition Referencesmentioning
confidence: 99%
“…[6,17,18] Policy and plan Formulation and implementation of policies and plans which the government announces for solid waste management and VSMSWPP management. [6,16,19,20] Laws Formulation and implementation of laws for solid waste management and the VSMSWPPs in the local area. [20][21][22] Public participation…”
Section: Key Success Factors Definition Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent articles (the leaves of the tree), studies were found where SV is analyzed from an environmental perspective (Chailertpong and Phimolsathien, 2018); Bowe and van der Horst, 2015;Fearne et al, 2012;Hsiao and Chuang, 2016;Trevena, Kaldor, and Downs, 2015), in the field of business (Biloslavo, Bagnoli, and Edgar, 2018;Kraus, Burtscher, Vallaster, and Angerer, 2018;Laasch, 2018;Morioka, Bolis, and de Carvalho, 2018;Tate and Bals, 2018) and in relation to the company's value chain (Tang, 2018;Rezaee, 2018;Berning and Venter, 2015;Markman and Krause, 2016;Muller, Vermeulen, and Glasbergen, 2012).…”
Section: Conceptmentioning
confidence: 99%